PENGARUH FAKTOR-FAKTOR PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KAMAR TAMU - Kamal, Farid; Kasmita, Kasmita; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This study is based on the decrease in occupancy rate of guest rooms from January toJune 2016. The purpose of research is to: (1) Knowing how a promotion at Savali Hotel Padang,(2) Knowing how the purchasing decision of the guest room at Savali Hotel Padang, (3)Analyze how the influence of factors in promotion of purchasing decision the guest room atSavali Hotel Padang, (4) Analyze how the influence of advertising against the decision ofpurchase the guest room at Savali Hotel Padang, (5) Analyze how a sales pitch against thedecision of the purchase the guest at Savali Hotel Padang, (6) Analyze how a marketing directlythe purchasing decision of the guest room at Savali Hotel Padang. This type research is a sort ofdescriptive set of quantitative.Technique Sampling is purposive sampling as many 83 people.The gathering data using the questionnaire based on the scale of likert that has proven itsvalidity and reliability. This research result indicates: (1) Promotion by Savali Hotel Padang,including category of pretty, with average scores 36,87%, (2) The Purchasing decision of theguest room at Savali Hotel Padang the categorized as well, an average score 52,6%, (3) Inpartial on 3 indicators, indicator of the most influential of the purchasing decision is an indicatordirect marketing by 1,120%, (4) The advertising effect negative with a value of 0,183%, (5) Thepromotion of sales to a positive effect on 0,980%, (6) Direct marketing have a positive influenceof 1,120%.Keywords: Promotion, Purchasing Decision